A restorative pedagogy for peace in the face of the pandemic and post pandemic: A community approach from teaching - de Mézerville López, Claire Marie (2020)
Abstract: Education in the context of SARS-CoV-2 has meant a crisis in educational systems confronted with emergency virtualization, distance education or the temporary suspension of the school year. In some countries, schools face the return to in person lessons under the enforcement of preventive protocols. This global emergency presents questions about how to respond from a propositive pedagogy and not just a reactive one, to face the current situation and anticipate the post pandemic scenery. This essay presents restorative practices as an approach that transcends disciplinary measures and constitutes a methodological ingredient for critical pedagogy and for peace. A restorative pedagogy is consolidated in the integration of community and the inputs from specialized experiences. Teaching and community implications are offered to the present and future responses from an affective citizenship perspective.